Observation of the $B^{0}_{s}→ J/ψK_{\rm S}^{0} K^{±} π^{\mp}$ decay - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; et al. (Springer Verlag, 2014)
Decays of the form $B^{0}_{(s)}\rightarrow J/\psi K_{{\rm S}}^{0} h^+ h^{\left(\prime\right) -}$ ($h^{(\prime)} = K, \pi$) are searched for in proton-proton collision data corresponding to an integrated luminosity of $1.0 \, {\rm fb}^{-1}$ recorded with the LHCb detector. The first observation of the $B^{0}_{s}\rightarrow J/\psi K_{{\rm S}}^{0} K^{\pm} \pi^{\mp}$ decay is reported, with significance in excess of 10 standard deviations. The $B^{0}\rightarrow J/\psi K_{{\rm S}}^{0} K^{+} K^{-}$ decay is also observed for the first time. The branching fraction of $B^{0}\rightarrow J/\psi K_{{\rm S}}^{0} \pi^{+} \pi^{-}$ is determined, to significantly better precision than previous measurements, using $B^0 \rightarrow J/\psi K_{{\rm S}}^{0}$ as a normalisation channel. Branching fractions and upper limits of the other $B^{0}_{(s)}\rightarrow J/\psi K_{{\rm S}}^{0} h^+ h^{\left(\prime\right) -}$ modes are determined relative to that of the $B^{0}\rightarrow J/\psi K_{{\rm S}}^{0} \pi^{+} \pi^{-}$ decay.